Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
[tex]JL=54[/tex]
Step-by-step explanation:
We are given that K is the midpoint of JL. Using this information, we want to find JL.
By the definition of midpoint, this means that:
[tex]JK=KL[/tex]
Substitute them for their equations:
[tex]8x+11=14x-1[/tex]
Solve for x. Subtract 8x from both sides:
[tex]11=6x-1[/tex]
Add 1 to both sides:
[tex]6x=12[/tex]
And divide both sides by 6. Hence:
[tex]x=2[/tex]
JL is the sum of JK and KL. Hence:
[tex]JK+KL=JL[/tex]
Since JK = KL, substitute either one for the other:
[tex]JK+(JK)=2JK=JL[/tex]
Substitute JK for its equation:
[tex]2(8x+11)=JL[/tex]
Since we know that x = 2:
[tex]2(8(2)+11)=2(16+11)=2(27)=54=JL[/tex]
Thus:
[tex]JL=54[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.